Comparative analysis of coagulation and adsorption utilizing chitosan extracted from crabshells for the removal of copper in landfill leachate - Becina, Maria Eleanor A. (2012)
The study was conducted to investigate the performance of coagulation and adsorption for removing copper in landfill leachate. Alum was used as coagulant and chitosan (extracted from crab shells) coated clay was utilized as an adsorbent. Three types of clay were utilized to immobilize chitosan: commercially available bentonite, class A and class B clay which were sourced from Metro Clark Waste Management Corporation (MCWMC). The influence of time, leachate pH, and dose in the two processes were investigated. The process efficiency was determined by percent copper and color removal. For the coagulation process, 72% of copper was removed at 10 minutes and an optimum removal of 81% was achieved from 20 minutes onwards. Color removal was consistent at 95% regardless of the length of time. Dose and leachate pH were not affected by the length of time, resulting to a 100% copper removal even at 10 minutes. Base on the result, coagulant dose is inversely proportional to color removal. Highest color reduction was achieved at a coagulant dose of 0.0005 g/ml. Color did not varied much at leachate pH 4 and 6, achieving a color reduction of 92%. At leachate pH 8, color removal increased to 94%. for the adsorption process, time and leachate pH did not influence the percent copper removal for the chitosan coated clay samples, achieving 100% copper removal. Chitosan coated bentonite exhibited the lowest copper removal among the clay samples based on dose, exhibiting only 50% copper removal at 2.5 g/ml. For the three parameters, color removal peaked at 93%.
"October 2012."
Thesis (M.S. Environmental Engineering)--University of the Philippines, Diliman.
Keywords: Metro Clark Waste Management Corporation (MCWMC).; Coagulation; Adsorption; Sanitary landfills -- Assessment; Chitosan